2022
DOI: 10.3389/fpsyg.2022.1009305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a pedagogical approach to promoting academic integrity in higher education: An online induction program

Abstract: Academic integrity is at the heart of excellent education. However, resources explaining the concept tend to be definition-driven, while using complex language and sometimes even an austere tone designed to discourage students from breaches. This study aims to design and evaluate an online module at a UK University across 2 years, designed to improve students’ understanding of concepts of academic integrity and practice. The module includes a range of interactive resources (e.g., gamified quizzes and e-booklet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In this study, the resultant data gathered through NLP, and particularly visualisation of the data (see Table 3), afforded the course team insights into the prevalence of each engagement type and student perspectives of this engagement reflected in student feedback responses. Pedagogical approaches or practices being implemented in an educational institution can be evaluated based on their students' feedback (Sbaffi & Zhao, 2022). The results from this prototype can reflect the trends of student feedback and their engagement towards the practices being implemented in the university.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the resultant data gathered through NLP, and particularly visualisation of the data (see Table 3), afforded the course team insights into the prevalence of each engagement type and student perspectives of this engagement reflected in student feedback responses. Pedagogical approaches or practices being implemented in an educational institution can be evaluated based on their students' feedback (Sbaffi & Zhao, 2022). The results from this prototype can reflect the trends of student feedback and their engagement towards the practices being implemented in the university.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, online teaching also promotes flexibility while reducing expenses ( Xhaferi and Xhaferi, 2020 ; Weldon et al, 2021 ). In addition to flexibility, researchers argue that online platforms and technology applications provide students with additional resources ( Pokhrel and Chhetri, 2021 ; Sbaffi and Zhao, 2022 ) and enhance student academic achievements ( Younas et al, 2022 ). Similarly, Fatoni et al (2020) found that students can benefit from asynchronous materials (e.g., lecture recordings) to enhance their knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means promoting the comprehensive education of students, not only in terms of specialized professional knowledge, but also instilling in them a strong foundation of ethical values that foster their personal growth. Academic integrity is essential for education excellence ( Sbaffi and Zhao, 2022 ).…”
Section: Introductionmentioning
confidence: 99%